Gender bias and credit access - Steven Ongena; Alexander Popov (European Central Bank (ECB), 2015)
This paper studies the causal effect of gender bias on access to bank credit. We extract an exogenous measure of gender bias from survey responses by descendants of US immigrants on questions about the role of women in society. We then use data on 6,000 small business firms from 17 countries and find that in countries with higher gender bias, female-owned firms are more frequently discouraged from applying for bank credit and more likely to rely on informal finance. At the same time, loan rejection rates and terms on granted loans do not vary between male and female firm owners. These results are not driven by credit risk differences between female- and male-owned firms or by any idiosyncrasies in the set of countries in our sample. Overall, the evidence suggests that in high-gender bias countries, female entrepreneurs are more likely to opt out of the loan application process, even though banks do not appear to discriminate against females that apply for credit.
Keywords: G21; J16; N32; Z13; 330; Bank credit; Cultural bias; Female-owned firms; Gender-based discrimination